Предмет: Алгебра, автор: Аноним

упростить выражение tg(180+b)cos(180-b)/tg(270+b)cos(270+b)+tg(900-b)

Ответы

Автор ответа: palilov2436
0

tg(180+b)=tgb=sinb/cosb  cos(180-b)=-cosb  tg(270+b)=-ctgb=-cosb/sinb 

cos(270+b)=sinb  tg(900-b)=(tg900+tgb)/(1-tg900tgb)=|tg900=tg(180+4п)=tg180=0|=tgb

 

 tg(180+b)cos(180-b)/tg(270+b)cos(270+b)+tg(900-b)=

    sinb

 - -------cosb

    cosb                        sinb

----------------------- =------------------

    cosb                     cosb-tgb

- ---------sinb+tgb

    sinb

Похожие вопросы
Предмет: Математика, автор: Аноним